A new kind of computational biology : cellular automata based models for genomics and proteomics /: cellular automata based models for genomics and proteomics. (2018) - Chaudhuri, Parimal Pal, 1941-; Ghosh, Soumyabrata; Dutta, Adip; Choudhury, Somshubhro Pal
No abstract available